Leadership Strategies in Islamic High Schools to Improve Quality and Ensure the School’s Survival - Anastasia Syahidah Firdaus; Nono Hery Yoenanto (CV RIFAINSTITUT, 2026)
The progress and existence of an educational institution cannot be separated from the role of leaders in motivating all school members to achieve common goals, namely improving the quality and quality of education and the resources within it. To achieve this, a leader is needed who can create an effective leadership strategy for his school. This study aims to analyze the principal's strategy in improving the quality and maintaining the existence of the school. Narrative literature review is used as a method of data collection in this study. Based on the literature review that has been conducted, it was concluded that the principal should have good managerial skills and can be a role model for all school members. Fulfillment and attention to the needs of school members are important points in the principal's efforts to improve school quality